IMPLEMENTATION OF DIGITAL MARKETING ON CULINARY MSME OWNERS IN CIBINONG DISTRICT - Muhammad Rifkhi; Jenji Gunaedi Argo; Yuliniar Yuliniar (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya, 2022)
This research uses a qualitative method which aims to determine the understanding and knowledge, forms of utilization, and the impact of the application of digital marketing by culinary MSME owners in Cibinong District. Data collection techniques in this study used the method of observation and interviews. Interviews were conducted with 8 informants, namely 1 representative of the Department of Cooperatives and UMKM in Bogor Regency, 1 representative of UMKM leaders in Cibinong District, 3 owners of culinary SMEs and 3 customers. To prove the validity of the data in this study, the researchers used the method of triangulation of data and references. The data analysis technique uses data reduction, data presentation and conclusion drawing. Research results show that: (1) Culinary MSME owners in Cibinong District have fairly good knowledge and understanding of digital marketing. (2) The digital marketing media they use include the GoFood, GrabFood, and ShopeeFood mobile applications, as well as the Google My Business page. (3) The impact felt after implementing digital marketing is to increase sales which have an impact on income and assist in promotions that make their business more widely known.